Gender Stereotype in the Formulation of Crime of Rape: A Comparison of Criminal Code and Draft Criminal Code - Lalu Panca Tresna D; Abu Sa'it; Imas Octaviana Dewi; Lalu Rangga Satria Wijaya; Yuni Ristanti (Faculty of Law, University of Mataram, 2020)
Rape is one of the crimes that may embody stereotype gender, likewise in Indonesian Criminal Code. However there is development conception concerning crimes of rape put forward in The Draft of Criminal Code. This study aims to determine the different provision of crimes of rape in Criminal Code and The Draft Criminal Code. The result of this study concluded that the provision of rape in the Draft Criminal Code have more advance than the provision of rape in Criminal Code. The Draft Criminal Code has renounce crime of rape base on gender by not showing woman as the only victim of rape. Furthermore the provisions of rape in the draft criminal code have asserted method of rape that not only by intercourse. Therefore the provision of crime of rape in the draft criminal code can include rape whose victim are boys or men.